Ação antimicrobiana combinada de nisina e extratos de Spirulina platensis contra bactérias gram-positivas e gram-negativas - Carvalho, Luana de (2023)
In recent years, food consumers have been looking for microbiologically safe foods, but with a reduced concentration of synthetic additives. In this sense, the use of antimicrobial substances of natural origin has emerged. Another trend is the use of two or more antimicrobial compounds, which present synergistic action, in the control of foodborne pathogens. In this sense, the microalgae Spirulina platensis has been recognized for its high amount of phenolic compounds, which have antimicrobial properties. Antimicrobial peptides (bacteriocins) have also been trending in the control of foodborne pathogens. Therefore, the objective of this work was to evaluate the synergistic action of extracts of S. platensis and commercially used nisin in inhibiting the growth of Gram-positive (+) and Gram-negative (-) bacteria. Four extraction protocols of S. platensis compounds were performed, followed by the disc diffusion test for Gram-positive and Gram-negative bacteria, with a total of 24 Gram-positive and Gram-negative bacteria tested. Alcoholic acidformic acid-sonication extraction was selected because of its antimicrobial activity against 91% of the strains tested, with halo sizes ranging from 10 to 30 mm in the disk diffusion test. From these results, Escherichia coli, Listeria monocytogenes and Staphylococcus aureus bacteria were selected. The disk diffusion test was also performed with nisin BV® at a concentration of 12.5 mg/mL. Minimum Inhibitory Concentration (MIC) assays and the checkerboard test were performed. MIC values for isolated nisin ranged from 0.5 to 0.12 µg/mL and for the extract ranged from 0.5 to 0.06 µg/mL. When both compounds were combined, the values ranged from 0.12 to 0.0078 µg/mL. ICIF values ranged from 0.302 to 0.18 representing synergism between compounds. The microbial growth curve with the substances combined in the intervals of 0, 2, 6, 12 and 24 hours, showed efficiency in the microbial reduction when the compounds were used in the combined form. Flow Cytometry and Scanning Electron Microscopy (SEM) tests were performed to confirm the injury of the bacteria tested in the presence of combined antimicrobial compounds, Flow Cytometry was performed with the S. platensis extract separately and the SEM was performed from of the separate compounds and the combination of the two substances. In the Flow Cytometry analysis using propidium iodide, a displacement of the peak intensity of the fluorophore was observed, indicating an increase in the permeability of the bacterial membrane. In the observation carried out with SEM, extravasation of intracellular material was observed, suggesting the disruption of the cell membrane, especially when treated with S. platensis and nisin combined. These results suggest that the combination of S. platensis and nisin has potential for application in the food industry as an alternative to synthetic preservatives, since both substances have GRAS status (generally recognized as safe) and have shown antimicrobial action against important pathogens transmitted by foods, with synergy between them, enhancing their effects.